2015
DOI: 10.1007/s13187-015-0909-x
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives and Attitudes of Jordanian Male College Students on Breast Cancer Screening

Abstract: The purpose of this study is to understand the attitudes of young Jordanian men towards breast cancer screening practices. A qualitative descriptive design informed by Clendenin and Connelly was used. Thirty-seven in-depth semi-structured individual audiotaped interviews were conducted. The analysis of the men's attitudes toward breast cancer captures the perception that breast cancer is an illness that occurs mainly later in life. This was associated with the perception of negative impact of cancer diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…In general, our study pinpointed the low knowledge of male partners regarding BC. Similar findings were reported in Jeddah [13], Jordan [20], and in Ghana [21]. The present study documented the significant role of male partners’ knowledge in wives’ practices and attitudes towards BC.…”
Section: Discussionsupporting
confidence: 91%
“…In general, our study pinpointed the low knowledge of male partners regarding BC. Similar findings were reported in Jeddah [13], Jordan [20], and in Ghana [21]. The present study documented the significant role of male partners’ knowledge in wives’ practices and attitudes towards BC.…”
Section: Discussionsupporting
confidence: 91%
“…In the Middle East, socio-cultural factors influence women's view of breast cancer screening. For example, in Saudi Arabia, men directly influence women's decision making with regard to healthcare services and their own perceptions of self-care (Al- Dasoqi et al, 2017). Arab men perceive that their opinions and support are a major factor influencing female family members' participation in breast cancer screening, it is important that any program instituted to increase such screening participation be aimed at both men and women (Donnelly et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Other men indicated that they are not comfortable, especially if the test is being performed by a male health care worker. Men believed that breast cancer preventive practices must be performed in a similar context of women's religious and cultural background (Al- Dasoqi et al, 2017). Hence, there is an urgent need to pay more attention to spreading awareness among men, as they are associates, and they need to be armed with proper awareness (Adebimpe et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Jordanian males’ attitudes towards BC could be attributed to their perception that BC is rare in men. Improving males’ attitudes towards BC is important in encouraging female relatives seeking BC screening (Al Dasoqi et al., 2017) because negative attitudes towards BC were reported among young females (Alsaraireh & Darawad, 2019). Health education regarding cancer and other CNCDs is crucial for young adults (Al Dasoqi et al., 2017; Parmar et al., 2014) and including these topics in the curriculum may help in early detection and disease prevention (Abdo et al., 2019; Alsaraireh & Darawad, 2018).…”
Section: Discussionmentioning
confidence: 99%